Organic light emitting diode and its preparation method and application

By introducing weakly interacting P-type and N-type organic semiconductor compounds into the light-emitting layer of the organic light-emitting diode, the nitrogen atomic interval control interactions are used to control the interactions in the carbazole unit structure, the preparation complex and cost of organic light-emitting diodes in the prior art is solved. High problems achieve efficient and stable luminous performance.

CN115101684BInactive Publication Date: 2025-01-10SOUTH CHINA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210492857.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-07
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When the existing organic light emitting diodes improve the exciton utilization efficiency of thermally activated delayed fluorescent materials, there are problems such as complex preparation, high cost, poor material stability and large roll-off of luminous performance, which is difficult to meet the requirements of high efficiency, stability and low cost.

Method used

The P-type organic semiconductor compound and N-type organic semiconductor compound with weak interaction are introduced into the light-emitting layer of the organic light-emitting diode. By designing the nitrogen atomic interval of the carbazole unit structure, the expansion and vibration of the C-N bond is controlled, thereby weakening the dipole interaction, thereby reducing the dipole interaction. Improve energy transfer efficiency and reduce driving voltage.

Benefits of technology

The low efficiency roll-off and low driving voltage of organic light emitting diodes are achieved while maintaining high external quantum efficiency, simplifying the preparation process and reducing costs, and providing a stable blue-green OLED device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115101684B_ABST
    Figure CN115101684B_ABST
Patent Text Reader

Abstract

The present invention discloses an organic light emitting diode and a preparation method and application thereof. The composition of the organic light emitting diode of the present invention includes a substrate, an anode, a hole transport layer, a light emitting layer, an electron transport layer, a cathode buffer layer and a cathode which are stacked in sequence, wherein the components of the light emitting layer include a P-type organic semiconductor compound, an N-type organic semiconductor compound and an organic light emitting compound; and the P-type organic semiconductor compound is an organic compound containing two carbazole units, and the nitrogen atoms in the two carbazole units are separated by 3 to 5 benzene rings. The organic light emitting diode of the present invention uses a weakly interacting exciplex as the main material, so that it can not only have a lower efficiency roll-off and a lower driving voltage while still maintaining a higher device external quantum efficiency, but also has the advantages of simple preparation and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of light-emitting devices, and in particular to an organic light-emitting diode and a preparation method and application thereof. Background Art

[0002] Thermally activated delayed fluorescent materials have been widely studied due to their advantages of narrow spectral emission and wide color gamut in organic light-emitting diode devices. At present, molecular design is generally used to improve the theoretical and actual exciton utilization efficiency of thermally activated delayed fluorescent materials, but this method requires a series of organic synthesis reactions based on loads, so there are problems such as complex preparation, high production cost, poor material stability, and large roll-off of luminescence performance.

[0003] In order to better apply organic fluorescent materials to light-emitting devices, the requirements for the main materials in organic light-emitting diodes are becoming increasingly higher. For example, it needs to have a high triplet energy level to prevent triplet excitons from being captured, it needs to have a suitable energy level to reduce the injection barrier of electrons and holes, and it also needs to have excellent bipolar carrier transport characteristics and good stability. At the same time, in order to regulate the exciton radiation transition, exciton upconversion, energy transfer and other processes, it also needs a main material with a high efficiency reverse intersystem crossing rate to improve the performance of the overall light-emitting device.

[0004] Therefore, there is an urgent need to develop an organic light-emitting diode that has a suitable host material, is simple to prepare, has low cost, and can effectively improve the external quantum efficiency and stability of the light-emitting device. Summary of the invention

[0005] In order to overcome the problems existing in the prior art, the object of the present invention is to provide an organic light emitting diode and a preparation method and application thereof.

[0006] The inventive concept of the present invention is: the present invention introduces a P-type organic semiconductor compound and an N-type organic semiconductor compound (i.e., an exciplex) with weak interactions into the light-emitting layer of an organic light-emitting diode, and uses the exciplex with weak interactions as the main material of the organic light-emitting diode, thereby improving the external quantum efficiency, stability, current efficiency and other performances of the organic light-emitting diode. The present invention is specifically designed that the P-type organic semiconductor compound in the light-emitting layer contains multiple carbazole unit structures (especially, the P-type organic semiconductor compound only contains carbazole units with weaker electron donation, and does not contain other nitrogen-containing strong electron-donating groups such as aniline, acridine, indole and carbazole), and the nitrogen atoms on the carbazole unit structure are used as the main electron-donating groups of the material, and the nitrogen atoms on different carbazole unit structures are controlled to be separated by 3 to 5 benzene ring structures, so that the CN bond stretching vibration of the P-type organic semiconductor compound and the N-type organic semiconductor compound in the light-emitting layer after mixing is not affected or is less affected (that is, the stretching and torsion of the CN bond of the material itself after the two materials are blended is not affected), so that the dipole interaction force between the P-type organic semiconductor compound and the N-type organic semiconductor compound is weak, which helps to improve the efficiency of energy transfer or electron transfer of the organic light-emitting compound in the light-emitting layer, and achieve the effects of reducing the driving voltage of the organic light-emitting diode, alleviating efficiency roll-off and weakening quenching, and maintaining a higher external quantum efficiency. Therefore, the present invention uses weakly interacting exciplexes to enable the organic light-emitting diode device to have a lower efficiency roll-off and a lower driving voltage while still maintaining a higher device external quantum efficiency.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] In a first aspect, the present invention provides an organic light emitting diode, which includes a substrate, an anode, a hole transport layer, a light emitting layer, an electron transport layer, a cathode buffer layer and a cathode arranged in sequence from bottom to top, wherein the components of the light emitting layer include a P-type organic semiconductor compound, an N-type organic semiconductor compound and an organic light emitting compound; the P-type organic semiconductor compound is an organic compound containing two carbazole units, and the nitrogen atoms in the two carbazole units are separated by 3 to 5 benzene rings.

[0009] Preferably, the P-type organic semiconductor compound comprises at least one of the following compounds:

[0010]

[0011] Further preferably, the P-type organic semiconductor compound comprises at least one of the following compounds:

[0012]

[0013] Preferably, the N-type organic semiconductor compound comprises at least one of the following compounds:

[0014]

[0015] Further preferably, the N-type organic semiconductor compound is

[0016] Preferably, the organic light-emitting compound is an organic compound containing a 2CzBN light-emitting structural unit, and the 2CzBN light-emitting structural unit is as follows:

[0017] Specifically, the structure of the organic light-emitting compound contains a rigid planar light-emitting unit structure formed by a carbazole group and boron.

[0018] Further preferably, the organic light-emitting compound comprises at least one of the following compounds:

[0019]

[0020] More preferably, the organic light-emitting compound comprises at least one of the following compounds:

[0021]

[0022] Preferably, the mass of the organic light-emitting compound accounts for 0.8% to 1.2% of the total mass of the light-emitting layer.

[0023] More preferably, the mass of the organic light-emitting compound accounts for 0.9% to 1.1% of the total mass of the light-emitting layer.

[0024] Preferably, the mass ratio of the P-type organic semiconductor compound to the N-type organic semiconductor compound is 1:0.8 to 0.8:1.

[0025] Further preferably, the mass ratio of the P-type organic semiconductor compound to the N-type organic semiconductor compound is 1:0.9 to 0.9:1.

[0026] Preferably, the substrate is one of a glass substrate, a quartz substrate, a sapphire substrate, an alloy substrate, a pure metal substrate, and a polyester substrate.

[0027] Preferably, the polyester material is one of polyimide, polyethylene terephthalate, polyethylene terephthalate, and polyethylene naphthalate.

[0028] Further preferably, the substrate is a glass substrate.

[0029] Preferably, the anode is composed of one or more of indium tin oxide, fluorine-doped tin dioxide, zinc oxide, and indium gallium zinc oxide.

[0030] Further preferably, the anode is composed of indium tin oxide.

[0031] Preferably, the cathode buffer layer is composed of lithium fluoride.

[0032] Preferably, the cathode is composed of one of metal aluminum and aluminum alloy.

[0033] Preferably, the hole transport layer is composed of a P-type organic semiconductor compound, and the P-type semiconductor compound is at least one of the following compounds:

[0034]

[0035] Specifically, the material in the hole transport layer is one or more of 4,4'-cyclohexylbis[N,N-bis(4-methylphenyl)aniline] (TAPC), 4,4',4"-tri(carbazole-9-yl)triphenylamine (TCTA), and 9,9'-(1,3-phenyl)di-9H-carbazole (mCP).

[0036] Preferably, the electron transport layer is composed of an N-type organic semiconductor compound, and the N-type organic semiconductor compound is at least one of the following compounds:

[0037]

[0038] Specifically, the materials in the electron transport layer are one or more of 2,8-bis(diphenylphosphoryl)dibenzo[b,d]furan (PPF), bis[2-((oxy)diphenylphosphino)phenyl]ether (DPEPO), 3,3'-[5'-[3-(3-pyridyl)phenyl][1,1':3',1"-terphenyl]-3,3"-diyl]bipyridine (TmPyPB), and 1,3-bis(3,5-bipyridin-3-ylphenyl)benzene (B3PyPB).

[0039] In a second aspect, the present invention provides a method for preparing the above-mentioned organic light emitting diode, comprising the following steps:

[0040] A hole transport layer, a light emitting layer, an electron transport layer, a cathode buffer layer and a cathode are sequentially fabricated on a substrate material with an anode layer to obtain an organic light emitting diode.

[0041] Preferably, the manufacturing method is thermal evaporation, spin coating, brush coating, spray coating, dip coating, roller coating, printing or inkjet printing.

[0042] Further preferably, the manufacturing method is thermal evaporation, and the evaporation rate of the thermal evaporation is

[0043] Preferably, the light-emitting layer is evaporated by a co-evaporation method.

[0044] Specifically, the co-evaporation method is to load the P-type organic semiconductor compound, N-type organic semiconductor compound and organic light-emitting compound in the light-emitting layer into different evaporation source devices respectively, and evaporate them together, so as to prepare a light-emitting layer in which the P-type organic semiconductor compound, N-type organic semiconductor compound and organic light-emitting compound are evenly mixed.

[0045] Preferably, the hole transport layer has a thickness of 30 nm to 60 nm.

[0046] Preferably, the thickness of the light-emitting layer is 10 nm to 20 nm.

[0047] Preferably, the thickness of the electron transport layer is 30 nm to 60 nm.

[0048] Preferably, the cathode buffer layer has a thickness of 0.5 nm to 3.0 nm.

[0049] Preferably, the thickness of the cathode

[0050] In a third aspect, the present invention provides application of the organic light emitting diode in a light emitting device.

[0051] The beneficial effects of the present invention are:

[0052] The organic light emitting diode of the present invention uses a weakly interacting exciplex as a main material, which not only has a lower efficiency roll-off and a lower driving voltage while still maintaining a higher device external quantum efficiency, but also has the advantages of simple preparation and low cost.

[0053] Specifically, the present invention has the following advantages:

[0054] (1) The organic light emitting diode device of the present invention has a lower device efficiency roll-off, a lower driving voltage and a higher external quantum efficiency;

[0055] (2) The organic light-emitting diode of the present invention is easy to prepare, and the preparation materials do not contain precious metal elements, which is conducive to reducing the preparation cost of the device;

[0056] (3) The exciplex donor unit of the present invention only contains a carbazole unit with a weaker charge donation property, and when there are multiple carbazole units, the nitrogen atoms in the carbazole units need to be separated by three benzene rings or more, so that they have a relatively weak dipole interaction, thereby effectively improving the efficiency of energy transfer, thereby improving the luminescence efficiency and stability of the light-emitting device;

[0057] (4) The organic light-emitting diode of the present invention can not only utilize singlet and triplet excitons to radiate light at the same time, but also, under the condition of small roll-off, its external quantum efficiency can reach 28.8%, the turn-on voltage can be reduced to 2.6V, and the current efficiency and power efficiency can be further improved. Therefore, it can be considered to be a blue-green organic light-emitting diode (OLED) device with low turn-on voltage, high luminous efficiency and stability;

[0058] (5) The excimer complex of the organic light-emitting diode of the present invention is applicable to a variety of organic light-emitting compounds, and provides a simple idea and method for improving the stability and light-emitting performance of the organic light-emitting diode. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 It is the infrared spectra of ICzPh, PO-T2T and the composite of the two in Comparative Example 4.

[0060] Figure 2 This is the infrared spectra of BCzPh, PO-T2T and the composite of the two in Comparative Example 5.

[0061] Figure 3 This is the infrared spectra of p-PhBCzPh, PO-T2T and the composite of the two in Comparative Example 6.

[0062] Figure 4 It is an external quantum efficiency-brightness curve diagram of the organic light emitting diodes in Example 1, Comparative Example 1, and Comparative Example 2.

[0063] Figure 5 1 is a current efficiency-brightness curve diagram of the organic light emitting diodes in Example 1, Comparative Example 1, and Comparative Example 2.

[0064] Figure 6 The power efficiency-brightness curves of the organic light emitting diodes in Example 1, Comparative Example 1 and Comparative Example 2 are shown.

[0065] Figure 7 The organic light emitting diodes in Example 1, Comparative Example 1 and Comparative Example 2 are 2 Electroluminescence spectrum at current density of .

[0066] Figure 8The external quantum efficiency-brightness curves of the organic light emitting diodes in Example 2, Example 3, Comparative Example 2 and Comparative Example 3 are shown.

[0067] Fig. 9 The organic light emitting diodes in Example 2, Example 3, Comparative Example 2 and Comparative Example 3 are 2 Electroluminescence spectrum at current density of .

[0068] Fig.10 1 is a brightness-voltage curve diagram of the organic light emitting diodes in Example 2, Example 3, Comparative Example 2 and Comparative Example 3.

[0069] Fig.11 This is an external quantum efficiency-brightness curve of the organic light emitting diode in Example 4.

[0070] Fig.12 Graphs showing the voltage-current density curve and the voltage-brightness curve of the organic light emitting diode in Example 4.

[0071] Fig.13 The light emission spectra of the organic light emitting diode in Example 4 at different brightnesses.

[0072] Fig.14 This is a graph showing the external quantum efficiency-brightness of the organic light emitting diode in Example 5.

[0073] Fig.15 Graphs showing the voltage-current density curve and the voltage-brightness curve of the organic light emitting diode in Example 5.

[0074] Fig.16 The light emission spectra of the organic light emitting diode in Example 5 at different brightnesses.

[0075] Fig.17 It is the external quantum efficiency-brightness curve diagram of the organic light emitting diodes in comparative examples 4 to 6.

[0076] Fig.18 4 is a brightness-voltage curve diagram of the organic light emitting diodes in comparative examples 4 to 6. DETAILED DESCRIPTION

[0077] The present invention is further described in detail below through specific examples.

[0078] Example 1

[0079] An organic light emitting diode has a multilayer structure, which comprises an ITO conductive glass substrate, TAPC (thickness: 30 nanometers), mCP (thickness: 10 nanometers), a composite layer (thickness: 20 nanometers), PPF (thickness: 10 nanometers), B3PyPB (thickness: 40 nanometers), lithium fluoride (thickness: 1 nanometer), and aluminum (thickness: 1500 angstroms) arranged in sequence from bottom to top.

[0080] Among them, the composite is composed of p-PhBCzPh, PO-T2T and 2TCzBN, the mass ratio of p-PhBCzPh and PO-T2T1 is 1:1, the content of 2TCzBN in the composite is 1wt%, and the composite can be recorded as p-PhBCzPh:PO-T2T:1wt%2TCzBN.

[0081] A method for preparing an organic light emitting diode comprises the following steps:

[0082] 1) An ITO conductive glass substrate (with a specification of 30 mm×30 mm, an ITO thickness of about 90 nanometers, and a sheet resistance of about 20 ohms / square) was taken and ultrasonically cleaned with acetone, a micron-grade semiconductor detergent, deionized water, and isopropanol for 15 minutes in sequence to remove dirt on the surface of the substrate; then the substrate was placed in a constant temperature oven for drying at 80 degrees Celsius, and the dried ITO conductive glass substrate was treated with a plasma ignition device for 4 minutes (to further remove organic pollutants attached to the surface), thereby obtaining a pretreated ITO conductive glass substrate (i.e., a cleaned ITO conductive glass substrate);

[0083] 2) The pretreated ITO conductive glass substrate was transferred to a glove box that was anhydrous and oxygen-free and filled with high-purity nitrogen. Then, the ITO conductive glass substrate was placed in the vacuum coating chamber in the glove box. The mechanical pump and molecular pump were turned on. When the pressure in the coating chamber reached 4×10 -4 Pa high vacuum, start thermal evaporation of thin films and use a specific mask to sequentially evaporate P-type organic semiconductor compound TAPC (thickness: 30 nanometers), composite (thickness: 20 nanometers), N-type organic semiconductor barrier material PPF (thickness: 10 nanometers), N-type organic semiconductor transport material B3PyPB (thickness: 40 nanometers), cathode buffer layer material lithium fluoride (thickness: 1 nanometer), cathode material aluminum (thickness: 1500 angstroms) on an ITO conductive glass substrate to obtain an organic light-emitting diode;

[0084] The composite is composed of p-PhBCzPh, PO-T2T1 and 2TCzBN, the mass ratio of p-PhBCzPh to PO-T2T1 is 1:1, the content of 2TCzBN in the composite is 1wt%, and the co-evaporation method is used for evaporation; the evaporation rate of the organic layer (P-type organic semiconductor compound, composite, N-type organic semiconductor barrier material and N-type organic semiconductor transmission material) is controlled at The evaporation rate of lithium fluoride is controlled at The aluminum evaporation process is first Evaporation rate Then with The evaporation is completed at a rate of .

[0085] Example 2

[0086] An organic light emitting diode has a multilayer structure, which comprises an ITO conductive glass substrate, TAPC (thickness: 30 nanometers), mCP (thickness: 10 nanometers), a composite layer (thickness: 20 nanometers), PPF (thickness: 10 nanometers), B3PyPB (thickness: 40 nanometers), lithium fluoride (thickness: 1 nanometer), and aluminum (thickness: 1500 angstroms) arranged in sequence from bottom to top.

[0087] The composite is composed of mCTP, PO-T2T and 2TCzBN, the mass ratio of mCTP to PO-T2T is 1:1, the content of 2TCzBN in the composite is 1wt%, and the composite can be recorded as mCTP:PO-T2T:1wt%2TCzBN.

[0088] A method for preparing an organic light emitting diode comprises the following steps:

[0089] 1) An ITO conductive glass substrate (with a specification of 30 mm×30 mm, an ITO thickness of about 90 nanometers, and a sheet resistance of about 20 ohms / square) was taken and ultrasonically cleaned with acetone, a micron-grade semiconductor detergent, deionized water, and isopropanol for 15 minutes in sequence to remove dirt on the surface of the substrate; then the substrate was placed in a constant temperature oven for drying at 80 degrees Celsius, and the dried ITO conductive glass substrate was treated with a plasma ignition device for 4 minutes (to further remove organic pollutants attached to the surface), thereby obtaining a pretreated ITO conductive glass substrate (i.e., a cleaned ITO conductive glass substrate);

[0090] 2) The pretreated ITO conductive glass substrate was transferred to a glove box that was anhydrous and oxygen-free and filled with high-purity nitrogen. Then, the ITO conductive glass substrate was placed in the vacuum coating chamber in the glove box. The mechanical pump and molecular pump were turned on. When the pressure in the coating chamber reached 4×10 -4Pa high vacuum, start thermal evaporation of thin films and use a specific mask to sequentially evaporate P-type organic semiconductor compound TAPC (thickness: 30 nanometers), composite (thickness: 20 nanometers), N-type organic semiconductor barrier material PPF (thickness: 10 nanometers), N-type organic semiconductor transport material B3PyPB (thickness: 40 nanometers), cathode buffer layer material lithium fluoride (thickness: 1 nanometer), cathode material aluminum (thickness: 1500 angstroms) on an ITO conductive glass substrate to obtain an organic light-emitting diode;

[0091] The composite is composed of mCTP, PO-T2T and 2TCzBN, the mass ratio of mCTP to PO-T2T is 1:1, the content of 2TCzBN in the composite is 1wt%, and the composite is evaporated by a co-evaporation method; the evaporation rate of the organic layer (P-type organic semiconductor compound, composite, N-type organic semiconductor barrier material and N-type organic semiconductor transmission material) is controlled at The evaporation rate of lithium fluoride is controlled at The aluminum evaporation process is first Evaporation rate Then with The evaporation is completed at a rate of .

[0092] Example 3

[0093] An organic light emitting diode has a multilayer structure, which comprises an ITO conductive glass substrate, TAPC (thickness: 30 nanometers), mCP (thickness: 10 nanometers), a composite layer (thickness: 20 nanometers), PPF (thickness: 10 nanometers), B3PyPB (thickness: 40 nanometers), lithium fluoride (thickness: 1 nanometer), and aluminum (thickness: 1500 angstroms) arranged in sequence from bottom to top.

[0094] The composite is composed of mCTP4Ph, PO-T2T and 2TCzBN, the mass ratio of mCTP4Ph and PO-T2T is 1:1, the content of 2TCzBN in the composite is 1wt%, and the composite can be recorded as mCTP4Ph:PO-T2T:1wt%2TCzBN.

[0095] A method for preparing an organic light emitting diode comprises the following steps:

[0096] 1) An ITO conductive glass substrate (with a specification of 30 mm×30 mm, an ITO thickness of about 90 nanometers, and a sheet resistance of about 20 ohms / square) was taken and ultrasonically cleaned with acetone, a micron-grade semiconductor detergent, deionized water, and isopropanol for 15 minutes in sequence to remove dirt on the surface of the substrate; then the substrate was placed in a constant temperature oven for drying at 80 degrees Celsius, and the dried ITO conductive glass substrate was treated with a plasma ignition device for 4 minutes (to further remove organic pollutants attached to the surface), thereby obtaining a pretreated ITO conductive glass substrate (i.e., a cleaned ITO conductive glass substrate);

[0097] 2) The pretreated ITO conductive glass substrate was transferred to a glove box that was anhydrous and oxygen-free and filled with high-purity nitrogen. Then, the ITO conductive glass substrate was placed in the vacuum coating chamber in the glove box. The mechanical pump and molecular pump were turned on. When the pressure in the coating chamber reached 4×10 -4 Pa high vacuum, start thermal evaporation of thin films and use a specific mask to sequentially evaporate P-type organic semiconductor compound TAPC (thickness: 30 nanometers), composite (thickness: 20 nanometers), N-type organic semiconductor barrier material PPF (thickness: 10 nanometers), N-type organic semiconductor transport material B3PyPB (thickness: 40 nanometers), cathode buffer layer material lithium fluoride (thickness: 1 nanometer), cathode material aluminum (thickness: 1500 angstroms) on an ITO conductive glass substrate to obtain an organic light-emitting diode;

[0098] The composite is composed of mCTP4Ph, PO-T2T and 2TCzBN, the mass ratio of mCTP4Ph to PO-T2T is 1:1, the content of 2TCzBN in the composite is 1wt%, and the composite is evaporated by a co-evaporation method; the evaporation rate of the organic layer (P-type organic semiconductor compound, composite, N-type organic semiconductor barrier material and N-type organic semiconductor transmission material) is controlled at The evaporation rate of lithium fluoride is controlled at The aluminum evaporation process is first Evaporation rate Then with The evaporation is completed at a rate of .

[0099] Example 4

[0100] An organic light emitting diode has a multilayer structure, which comprises an ITO conductive glass substrate, TAPC (thickness: 30 nanometers), mCP (thickness: 10 nanometers), a composite layer (thickness: 20 nanometers), PPF (thickness: 10 nanometers), B3PyPB (thickness: 40 nanometers), lithium fluoride (thickness: 1 nanometer), and aluminum (thickness: 1500 angstroms) arranged in sequence from bottom to top.

[0101] Among them, the composite is composed of p-PhBCzPh, PO-T2T and DMAC-2TCzBN, and the mass ratio of p-PhBCzPh and PO-T2T is 1:1, the content of DMAC-2TCzBN in the composite is 1wt%, and the composite can be recorded as p-PhBCzPh:PO-T2T:1wt%DMAC-2TCzBN.

[0102] A method for preparing an organic light emitting diode comprises the following steps:

[0103] 1) An ITO conductive glass substrate (with a specification of 30 mm×30 mm, an ITO thickness of about 90 nanometers, and a sheet resistance of about 20 ohms / square) was taken and ultrasonically cleaned with acetone, a micron-grade semiconductor detergent, deionized water, and isopropanol for 15 minutes in sequence to remove dirt on the surface of the substrate; then the substrate was placed in a constant temperature oven for drying at 80 degrees Celsius, and the dried ITO conductive glass substrate was treated with a plasma ignition device for 4 minutes (to further remove organic pollutants attached to the surface), thereby obtaining a pretreated ITO conductive glass substrate (i.e., a cleaned ITO conductive glass substrate);

[0104] 2) The pretreated ITO conductive glass substrate was transferred to a glove box that was anhydrous and oxygen-free and filled with high-purity nitrogen. Then, the ITO conductive glass substrate was placed in the vacuum coating chamber in the glove box. The mechanical pump and molecular pump were turned on. When the pressure in the coating chamber reached 4×10 -4 Pa high vacuum, start thermal evaporation of thin films and use a specific mask to sequentially evaporate P-type organic semiconductor compound TAPC (thickness: 30 nanometers), composite (thickness: 20 nanometers), N-type organic semiconductor barrier material PPF (thickness: 10 nanometers), N-type organic semiconductor transport material B3PyPB (thickness: 40 nanometers), cathode buffer layer material lithium fluoride (thickness: 1 nanometer), cathode material aluminum (thickness: 1500 angstroms) on an ITO conductive glass substrate to obtain an organic light-emitting diode;

[0105] The composite is composed of p-PhBCzPh, PO-T2T and DMAC-2TCzBN, the mass ratio of p-PhBCzPh to PO-T2T is 1:1, the content of DMAC-2TCzBN in the composite is 1wt%, and the composite is evaporated by a co-evaporation method; the evaporation rate of the organic layer (P-type organic semiconductor compound, composite, N-type organic semiconductor barrier material and N-type organic semiconductor transmission material) is controlled at The evaporation rate of lithium fluoride is controlled at The aluminum evaporation process is first Evaporation rate Then with The evaporation is completed at a rate of .

[0106] Example 5

[0107] An organic light emitting diode has a multilayer structure, which comprises an ITO conductive glass substrate, TAPC (thickness: 30 nanometers), mCP (thickness: 10 nanometers), a composite layer (thickness: 20 nanometers), PPF (thickness: 10 nanometers), B3PyPB (thickness: 40 nanometers), lithium fluoride (thickness: 1 nanometer), and aluminum (thickness: 1500 angstroms) arranged in sequence from bottom to top.

[0108] Among them, the composite is composed of p-PhBCzPh, PO-T2T and DMACTCzBN, and the mass ratio of p-PhBCzPh and PO-T2T is 1:1, the content of DMACTCzBN in the composite is 1wt%, and the composite can be recorded as p-PhBCzPh:PO-T2T:1wt%DMACTCzBN.

[0109] A method for preparing an organic light emitting diode comprises the following steps:

[0110] 1) An ITO conductive glass substrate (with a specification of 30 mm×30 mm, an ITO thickness of about 90 nanometers, and a sheet resistance of about 20 ohms / square) was taken and ultrasonically cleaned with acetone, a micron-grade semiconductor detergent, deionized water, and isopropanol for 15 minutes in sequence to remove dirt on the surface of the substrate; then the substrate was placed in a constant temperature oven for drying at 80 degrees Celsius, and the dried ITO conductive glass substrate was treated with a plasma ignition device for 4 minutes (to further remove organic pollutants attached to the surface), thereby obtaining a pretreated ITO conductive glass substrate (i.e., a cleaned ITO conductive glass substrate);

[0111] 2) The pretreated ITO conductive glass substrate was transferred to a glove box that was anhydrous and oxygen-free and filled with high-purity nitrogen. Then, the ITO conductive glass substrate was placed in the vacuum coating chamber in the glove box. The mechanical pump and molecular pump were turned on. When the pressure in the coating chamber reached 4×10 -4 Pa high vacuum, start thermal evaporation of thin films and use a specific mask to sequentially evaporate P-type organic semiconductor compound TAPC (thickness: 30 nanometers), composite (thickness: 20 nanometers), N-type organic semiconductor barrier material PPF (thickness: 10 nanometers), N-type organic semiconductor transport material B3PyPB (thickness: 40 nanometers), cathode buffer layer material lithium fluoride (thickness: 1 nanometer), cathode material aluminum (thickness: 1500 angstroms) on an ITO conductive glass substrate to obtain an organic light-emitting diode;

[0112] The composite is composed of p-PhBCzPh, PO-T2T and DMACTCzBN, the mass ratio of p-PhBCzPh to PO-T2T is 1:1, the content of DMACTCzBN in the composite is 1wt%, and the composite is evaporated by a co-evaporation method; the evaporation rate of the organic layer (P-type organic semiconductor compound, composite, N-type organic semiconductor barrier material and N-type organic semiconductor transmission material) is controlled at The evaporation rate of lithium fluoride is controlled at The aluminum evaporation process is first Evaporation rate Then with The evaporation is completed at a rate of .

[0113] Comparative Example 1

[0114] This comparative example provides an organic light-emitting diode, which is different from Example 1 in that the composite consists of mCBP and 2TCzBN, wherein the content of 2TCzBN is 1 wt %, and the composite can be recorded as mCBP: 1 wt % 2TCzBN.

[0115] Comparative Example 2

[0116] This comparative example provides an organic light-emitting diode, which is different from Example 1 in that the composite consists of mCBP, PO-T2T and 2TCzBN, wherein the content of 2TCzBN is 1 wt %, and the composite can be recorded as mCBP:PO-T2T:1 wt % 2TCzBN.

[0117] Comparative Example 3

[0118] This comparative example provides an organic light-emitting diode, which is different from Examples 1 to 3 in that the composite consists of mCP, PO-T2T and 2TCzBN, wherein the content of 2TCzBN is 1 wt %, and the composite can be recorded as mCP: PO-T2T: 1 wt % 2TCzBN.

[0119] Comparative Example 4

[0120] This comparative example provides an organic light emitting diode, which is different from Examples 1 to 3 in that the composite consists of ICzPh and PO-T2T, and the composite can be recorded as ICzPh:PO-T2T.

[0121] Comparative Example 5

[0122] This comparative example provides an organic light emitting diode, which is different from Examples 1 to 3 in that the composite consists of BCzPh and PO-T2T, and the composite can be recorded as BCzPh:PO-T2T.

[0123] Comparative Example 6

[0124] This comparative example provides an organic light emitting diode, which is different from Examples 1 to 3 in that the composite consists of p-PhBCzPh and PO-T2T, and the composite can be recorded as p-PhBCzPh:PO-T2T.

[0125] It should be noted that the preparation method of the organic light-emitting diodes in Comparative Examples 1 to 6 is similar to that in the embodiment, except that the composite materials in the light-emitting layer are different. At the same time, the thickness of the evaporated layer is monitored in real time by a quartz crystal film thickness detector during the evaporation process. Moreover, the organic light-emitting diode in the present invention can selectively add buffer layer materials on both the anode and cathode sides. The evaporated layer prepared by thermal evaporation in the organic light-emitting diode in the present invention can also be prepared by solution processing methods such as spin coating, brush coating, spray coating, dip coating, roller coating, screen printing, printing or inkjet printing.

[0126] The N-type organic semiconductor barrier material and the N-type organic semiconductor transport material in the embodiments and comparative examples are both N-type organic semiconductor compounds, belonging to the electron transport layer in the organic light emitting diode; the composite in the embodiments and comparative examples is the light emitting layer in the organic light emitting diode.

[0127] It should also be noted that the structural formulas of the raw materials used in Comparative Examples 1 to 6 are specifically as follows:

[0128]

[0129] Performance Testing

[0130] After the above-mentioned organic light-emitting diode device is prepared, the device is taken out of the evaporation cavity, and a glass cover is used to simply encapsulate it in a glove box using an epoxy resin encapsulation glue. Then it is taken out for testing in the air. The test equipment is a CS200 brightness meter generated by Konica-Minolta, and the device current and voltage information is measured by a 2400 source meter generated by Keithley. The current efficiency and power efficiency of the device can be calculated respectively by information such as brightness, current, and voltage. Under the assumption of Lambertian distribution, the external quantum efficiency of the device is calculated based on brightness, current density, and electroluminescence spectrum. The electroluminescence spectrum of the device is obtained by testing the PR745 device generated by PhotoResearch.

[0131] 1) Performance test results of the organic light emitting diodes in Examples 1 to 5 and Comparative Examples 1 to 6 are shown in Table 1. The performance of different organic light emitting diodes at maximum efficiency, 100 cd·m -2 、1000cd·m -2 The device performance parameters under the following conditions are shown in Table 2.

[0132] Table 1 Device performance parameters of organic light emitting diodes in Examples 1 to 5 and Comparative Examples 1 to 6 under maximum efficiency conditions

[0133]

[0134]

[0135] Table 2 Different organic light-emitting diodes at maximum efficiency, 100 cd·m -2 、1000cd·m -2 Device performance parameters under conditions

[0136]

[0137] It can be seen from Table 1 that by comparing the device performances of Example 1, Comparative Example 1 and Comparative Example 2, it is found that only when an organic light-emitting diode has a pair of p-PhBCzPh and PO-T2T with weak interaction, it can obtain higher current efficiency, external quantum efficiency and power efficiency at a lower turn-on voltage (2.6V).

[0138] By comparing the device performance of Example 2, Example 3, Comparative Example 2 and Comparative Example 3, it is also found that only by adding a pair of N-type organic semiconductor compounds and P-type organic semiconductor compounds with weak interaction in the light-emitting layer can the light-emitting performance of the organic light-emitting diode be further improved. That is, the P-type organic semiconductor compound with weak interaction needs to be composed of carbazole units, and the nitrogen atoms in the P-type organic semiconductor compound need to be separated by three to five benzene rings to form a weak interaction force with the N-type organic semiconductor compound.

[0139] It can be seen from the device performance of Comparative Examples 4, 5 and 6 that: in the case of no addition of light-emitting materials, the measured current efficiency, external quantum efficiency and power efficiency of the organic light-emitting diodes at a higher turn-on voltage (3.2V) are all lower than those of Examples 1 to 5. This is because the nitrogen atoms in the P-type organic semiconductor compounds of Comparative Examples 4 and 5 are closely spaced, resulting in a stronger interaction force between them and the N-type organic semiconductor compounds, which in turn results in the current efficiency, external quantum efficiency and power efficiency of Comparative Examples 4 and 5 being lower than those of Comparative Example 6.

[0140] It can be seen from Table 2 that by observing the changes in device performance tested under different conditions, it can be concluded that the performance of the organic light-emitting diode in Example 1 changes less, thus having a lower roll-off and more stable performance. At the same time, it can be seen from the performance data of the organic light-emitting diodes in Examples 4 and 5 that the present invention adds a pair of N-type organic semiconductor compounds and P-type organic semiconductor compounds with weak interactions in the light-emitting layer, thereby improving the stability and efficiency of organic light-emitting compounds such as 2TCzBN, DMAC-2TCzBN, and DMACTCzBN, and can be applied to different organic light-emitting compounds.

[0141] 2) Since the P-type organic semiconductor compounds ICzPh, BCzPh, and p-PhBCzPh in the complex contain electron-donating groups, and the N-type organic semiconductor compound PO-T2T in the complex contains electron-withdrawing groups, the P-type organic semiconductor compound in the complex can generate an attractive interaction force with the N-type organic semiconductor compound, and this force is called a dipole interaction force. In the infrared spectrum, the dipole interaction force at 1445 cm -1 -1455cm -1 The characteristic peak belongs to the signal peak of CN bond stretching vibration in P-type organic semiconductor compounds ICzPh, BCzPh, and p-PhBCzPh. Therefore, the influence of dipole interaction force on N-type organic semiconductor compounds can be observed by observing the infrared spectrum signal.

[0142] The infrared spectra of ICzPh, PO-T2T and the composite of the two in Comparative Example 4 are as follows: Figure 1 The infrared spectra of BCzPh, PO-T2T and the composite of the two in Comparative Example 5 are shown in FIG. Figure 2 The infrared spectra of p-PhBCzPh, PO-T2T and the composite of the two in Comparative Example 6 are shown in FIG. Figure 3 shown.

[0143] Depend on Figure 1 , Figure 2 , Figure 3 From Table 1, we can see that the mixture of ICzPh and PO-T2T (i.e., ICzPh+PO-T2T) has a peak at 1445 cm -1 -1455cm -1 The signal peak (peak shape and peak intensity) at the wave number of is significantly different from the infrared spectrum characterization signal of pure ICzPh, so the CN bond stretching vibration in the P-type organic semiconductor compound ICzPh is greatly affected in the composite, and the dipole interaction force between it and PO-T2T is strong. Similarly, the CN bond stretching vibration in the P-type organic semiconductor compound BCzPh is greatly affected in the composite, and the dipole interaction force between it and PO-T2T is strong.

[0144] At the same time, the Fourier transform infrared spectroscopy also found that the mixture of p-PhBCzPh and PO-T2T (i.e., p-PhBCzPh+PO-T2T) was located at 1445 cm -1 -1455cm -1 The signal peak (peak shape and peak intensity) of the composite has no obvious change compared with that of pure p-PhBCzPh. Therefore, the stretching vibration of the CN bond in the P-type organic semiconductor compound p-PhBCzPh in the composite is not affected or is slightly affected, and the dipole interaction force between it and PO-T2T is weak.

[0145] By characterizing the dipole interaction force, comparing device performance and observing the structural differences among P-type organic semiconductor compounds ICzPh, BCzPh, and p-PhBCzPh, it can be verified that a pair of weakly interacting complexes can be beneficial to improving the performance of light-emitting devices. The complex is composed of a P-type organic semiconductor compound and an N-type organic semiconductor compound, wherein the P-type organic semiconductor contains multiple carbazole groups, and the spacing between the N atoms on the carbazole unit needs to be greater than three benzene rings (preferably three to five benzene rings).

[0146] The external quantum efficiency-brightness curves of the organic light emitting diodes in Comparative Examples 4 to 6 are as follows: Fig.17 The brightness-voltage curves of the organic light emitting diodes in Comparative Examples 4 to 6 are shown in FIG. Fig.18 shown.

[0147] Depend on Fig.17 , Fig.18 As can be seen from Table 1, the performances of organic light-emitting diodes composed of complexes of P-type organic semiconductor compounds ICzPh (containing indolecarbazole units, and the distance between nitrogen atoms is one benzene ring), BCzPh (containing only carbazole units, but the distance between nitrogen atoms is two benzene rings), and p-PhBCzPh (the distance between nitrogen atoms is three benzene rings) and N-type organic semiconductor compound PO-T2T are compared. It is found that the device composed of the complex formed by p-PhBCzPh and PO-T2T has excellent luminescence performance (i.e., higher external quantum efficiency and lower voltage required to achieve the same brightness), which once again verifies that the inventive concept of the present invention is highly feasible and supported by relevant experimental data.

[0148] 3) The external quantum efficiency-brightness curves of the organic light emitting diodes in Example 1, Comparative Example 1 and Comparative Example 2 are as follows: Figure 4 The current efficiency-brightness curves of the organic light emitting diodes in Example 1, Comparative Example 1 and Comparative Example 2 are shown in FIG. Figure 5 The power efficiency-brightness curves of the organic light emitting diodes in Example 1, Comparative Example 1 and Comparative Example 2 are shown in FIG. Figure 6The organic light emitting diodes in Example 1, Comparative Example 1 and Comparative Example 2 are 2 The electroluminescence spectrum at a current density of Figure 7 shown.

[0149] Depend on Figure 4 , Figure 5 , Figure 6 It can be seen that: under the same brightness, compared with comparative examples 1 and 2, the external quantum efficiency, current efficiency and power efficiency of the organic light emitting diode in Example 1 are higher, and the external quantum efficiency can reach 25.7%, and the current efficiency can reach 53.4 cd·A -1 , power efficiency can reach 62.5lm W -1 . Figures 4 to 6 The necessity of the simultaneous presence of p-PhBCzPh and PO-T2T in the light-emitting layer is demonstrated.

[0150] Depend on Figure 7 It can be seen that: from the organic light emitting diode at 1mA / m 2 From the electroluminescence spectrum under the current density of , the normalized electroluminescence spectrum shows that the organic light emitting diodes in Example 1, Comparative Example 1 and Comparative Example 2 all have a strong signal peak at 400nm~600nm, indicating that these organic light emitting diodes are all blue-green light OLED devices.

[0151] 4) External quantum efficiency-brightness curves of the organic light emitting diodes in Example 2, Example 3, Comparative Example 2 and Comparative Example 3, as shown in FIG. Figure 8 The organic light emitting diodes in Example 2, Example 3, Comparative Example 2 and Comparative Example 3 were 2 The electroluminescence spectrum at a current density of Fig. 9 The brightness-voltage curves of the organic light emitting diodes in Example 2, Example 3, Comparative Example 2 and Comparative Example 3 are shown in FIG. Fig.10 shown.

[0152] Depend on Figure 8 , Fig. 9 , Fig.10 It can be seen that: from the perspective of device external quantum efficiency, the maximum external quantum efficiency of the device with a light-emitting layer of p-PhBCzPh:PO-T2T:1wt%DMAC-2TCzBN is 22.7%, and the maximum external quantum efficiency of the device with a light-emitting layer of p-PhBCzPh:PO-T2T:1wt%DMACTCzBN is 24.2%, which shows that devices based on weakly interacting complexes can achieve higher device external quantum efficiency in different light-emitting materials. At the same time, from the data of current efficiency and power efficiency, devices based on weakly interacting complexes can achieve higher current efficiency and power efficiency in different light-emitting materials.

[0153] From an organic light emitting diode at 1mA / m 2 From the electroluminescence spectrum under the current density of , the normalized electroluminescence spectrum shows that the organic light emitting diodes in Example 2, Example 3, Comparative Example 2 and Comparative Example 3 all have a strong signal peak at 400nm~600nm, indicating that these organic light emitting diodes are all blue-green light OLED devices.

[0154] 5) The external quantum efficiency-brightness curve of the organic light emitting diode in Example 4, as shown in FIG. Fig.11 The voltage-current density curve and voltage-brightness curve of the organic light emitting diode in Example 4 are shown in FIG. Fig.12 The luminescence spectra of the organic light emitting diode in Example 4 at different brightness are shown in FIG. Fig.13 The external quantum efficiency-brightness curve of the organic light emitting diode in Example 5 is shown in FIG. Fig.14 The voltage-current density curve and voltage-brightness curve of the organic light emitting diode in Example 5 are shown in FIG. Fig.15 The luminescence spectra of the organic light emitting diode in Example 5 at different brightness are shown in FIG. Fig.16 shown.

[0155] Depend on Figure 8 , Figures 11 to 16 It can be seen that from the efficiency roll-off of the device, the device with the light-emitting layer of p-PhBCzPh:PO-T2T:1wt%DMAC-2TCzBN has an efficiency of 100 cd / m 2 The external quantum efficiency measured under the conditions is 20.0%, and the light-emitting layer p-PhBCzPh:PO-T2T:1wt%DMACTCzBN is 100cd / m 2 The external quantum efficiency measured under the conditions is 19.6%. Compared with DMAC-2TCzBN and DMACTCzBN, they have a smaller roll-off (i.e., the external quantum efficiency decreases more slowly), which shows that the device based on the weak interaction complex (p-PhBCzPh and PO-T2T) exhibits a low efficiency roll-off and still maintains the advantage of high device efficiency at high brightness. At the same time, from the voltage-current density curve and the voltage-brightness curve, the organic light-emitting diodes in Examples 4 and 5 can achieve the effects of higher current density and greater brightness at a lower voltage. In addition, from the luminescence spectrum under different brightness, the wavelength and regularity of the luminescence signal of the organic light-emitting diodes in Examples 4 and 5 are basically consistent at different brightnesses, indicating that the luminescence stability of the organic light-emitting diodes is very good.

[0156] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. An organic light emitting diode, comprising a substrate, an anode, a hole transport layer, a light emitting layer, an electron transport layer, a cathode buffer layer and a cathode stacked in sequence, characterized in that: The components of the light-emitting layer include a P-type organic semiconductor compound, an N-type organic semiconductor compound and an organic light-emitting compound; The P-type organic semiconductor compound is at least one of the following compounds: ; The N-type organic semiconductor compound is at least one of the following compounds: ; The organic light-emitting compound is an organic compound containing a 2CzBN light-emitting unit, and the 2CzBN light-emitting unit is as follows: .

2. The organic light emitting diode according to claim 1, characterized in that: The substrate is one of a glass substrate, a quartz substrate, a sapphire substrate, an alloy substrate, a pure metal substrate, and a polyester substrate; the component of the anode is one or more of indium tin oxide, fluorine-doped tin dioxide, zinc oxide, and indium gallium zinc oxide; the component of the cathode buffer layer is lithium fluoride; and the component of the cathode is one of metal aluminum and aluminum alloy.

3. The organic light emitting diode according to claim 1, characterized in that: The hole transport layer is composed of a P-type organic semiconductor compound, and the P-type organic semiconductor compound is at least one of the following compounds: 。 4. The organic light emitting diode according to claim 1, characterized in that: The electron transport layer is composed of an N-type organic semiconductor compound, and the N-type organic semiconductor compound is at least one of the following compounds: 。 5. The method for preparing an organic light emitting diode according to any one of claims 1 to 4, characterized in that: The following steps are involved: A hole transport layer, a light emitting layer, an electron transport layer and a cathode are sequentially fabricated on a substrate material with an anode layer to obtain an organic light emitting diode.

6. The method for preparing an organic light emitting diode according to claim 5, characterized in that: The manufacturing method is thermal evaporation, spin coating, brush coating, spray coating, dip coating, roller coating, printing or inkjet printing.

7. Use of the organic light emitting diode according to any one of claims 1 to 4 in a light emitting device.

Citation Information

Patent Citations

  • Efficient fluorescent organic light-emitting diode and preparation method thereof

    CN109713166A

  • Organic electroluminescent device and organic compound

    CN113999162A